Rethinking LoRa for the IoT : an information-centric approach - Peter Kietzmann and Jose Alamos and Dirk Kutscher and Thomas C. Schmidt and Matthias Wählisch (IEEE communications magazine, 2023)
In this paper, we present LoRa-ICN, a new long-range communication system that provides a versatile data-oriented integration of battery-driven LoRa nodes into the Internet of Things (IoT). LoRa-ICN builds on two paradigms: Information-centric Networking (ICN), which enables more direct, data-oriented communication between Internet systems and the low-power wireless domain, and 802.15.4~DSME, which is an IoT MAC layer that facilitates reliable LoRa transmissions. While the combination of LoRa and DSME is generally better suited for bi-directional end-to-end communication, it still incurs considerable long and variable transmission latencies, and challenges the network layer transition between the power-constrained wireless domain and the Internet. Our design and implementation on actual off-the-shelf IoT hardware includes extensions to ICN that enable delay-tolerant data retrieval between LoRa nodes and an application on the Internet. An experimental comparison between default ICN mechanisms and our extensions shows that LoRa-ICN is able to achieve a high data delivery rate, while dealing with the higher latencies explicitly, thus providing a viable option for re-imaginig LoRa networks with a data-oriented, Internet-friendly approach.